Faktor-faktor yang menyumbang kepada hubungan kesejahteraan isi rumah - Shapee, Nur Amira Syafiqah (2017)
Most of the housing policies are established to meet the housing needs for the middle and lower income groups. Besides, housing policy is formed to help the lower-income households to own a house at their affordable rate. However, due to the rapid increased in house prices compared to household income, this situation has indirectly pressured certain type of household to own a house. Most of the house prices in the market are beyond the household affordability which may affect to household’s well-being. This research was conducted with three objectives. The first objective is to identify characteristics of housing ownership that leads to household well-being. The second objective is to identify the factors that contributed to the household’s well-being and the third objective is to evaluate the relationship between factors that contributed to household’s well-being. In order to achieve these three objectives, primary and secondary data is used in this study. The secondary data was acquired from literatures review to establish the theory of the study. While, primary data was gathered from field study by distributing questionnaires to the targeted respondent who are from Kuala Lumpur’s middle and lower bumiputera household income. The collected primary data were analysed by using descriptive statistical methods including frequency, Likert Scale data analysis, degree of importance of factors, cross tabulation and chi-square. The results from the analysis shows that the criteria for household’s well-being in housing affordability ownership are encompassing a comfortable lifestyle without having pressure which is satisfaction, living in a harmony and peace, households are unaffected by other living cost and has easy access to buy or rent an affordable home based on income ability, purchasing and repayment capability. While the factors that influenced household’s well-being are repayment of housing loan, housing prices, income, household expenditure, public facilities, community safety and lifestyle, education and intellectual, socio-cultural and political. From the analysis, it is concluded that there are four factors of social well-being groups that have a significant relationship to all of the factors of economic well-being groups namely public facilities, community safety and lifestyle, education and intellectual development as well as age. Thus, this research has contributed to the expansion of knowledge, especially on well-being and provides the ideas and benchmarks to the policy makers on the concept of household well-being.